Neuronal IGF-1 overexpression restores hippocampal newborn cell survival and recent CFC memory consolidation in Cav1.3 knock-out mice - Kim, Su-Hyun; Kim, Chong-Hyun (Elsevier BV, 2024)
Insulin-like growth factor-1 (IGF-1) exogenously supplied in the brain was shown to enhance the survival of hippocampal dentate gyrus (DG) newborn cells and some cognitive functions of mice. This study aims to test whether IGF-1 requires Cav1.3 activity critically while enhancing newborn cell survival and cognitive functions. We used Cav1.3 KO mice, where both DG newborn cell survival and the recent (1 day) single-trial contextual fear conditioning (CFC) memory consolidation were impaired. To supply IGF-1, we overexpressed (OX) IGF-1 in DG mature neurons by injecting an adeno-associated virus (AAV-IGF-1-mCherry) into the hippocampal areas of Cav1.3 KO mice. Our results, first, confirmed the enhanced expression of IGF-1 in the DG granule cell layer by immunohistochemistry. Next, we found this IGF-1 OX resulted in fully restoring both the survival rate of DCX (+) newborn cells and the recent single-trial CFC memory formation in Cav1.3 KO mice. Our results show that IGF-1 can enhance the survival of DG immature newborn cells and the recent CFC memory formation in a Cav1.3 channel-independent manner in vivo, suggesting activation of complementary pathways including the Cav1.2 channel. The result will help the application of adult newborn cell-based therapy improve the cognitive functions of neurological disorders.